Plastic footprint deteriorates dryland carbon footprint across soil–plant-atmosphere continuum - Meng-Ying Li; Wei Wang; Yue Ma; Yinglong Chen; Hong-Yan Tao; Ze-Ying Zhao; Peng-Yang Wang; Li Zhu; Baoluo Ma; Yun-Li Xiao; Shi-Sheng Li; Muhammad Ashraf; et al. (Environment International, 2024)
Plastic fragments are widely found in the soil profile of terrestrial ecosystems, forming plastic footprint and posing increasing threat to soil functionality and carbon (C) footprint. It is unclear how plastic footprint affects C cycling, and in particularly permanent C sequestration. Integrated field observations (including 13C labelling) were made using polyethylene and polylactic acid plastic fragments (low-, medium- and high-concentrations as intensifying footprint) landfilling in soil, to track C flow along soil–plant-atmosphere continuum (SPAC). The result indicated that increased plastic fragments substantially reduced photosynthetic C assimilation (p < 0.05), regardless of fragment degradability. Besides reducing C sink strength, relative intensity of C emission increased significantly, displaying elevated C source. Moreover, root C fixation declined significantly from 21.95 to 19.2 mg m−2, and simultaneously root length density, root weight density, specific root length and root diameter and surface area were clearly reduced. Similar trends were observed in the two types of plastic fragments (p > 0.05). Particularly, soil aggregate stability was significantly lowered as affected by plastic fragments, which accelerated the decomposition rate of newly sequestered C (p < 0.05). More importantly, net C rhizodeposition declined averagely from 39.77 to 29.41 mg m−2, which directly led to significant decline of permanent C sequestration in soil. Therefore, increasing plastic footprint considerably worsened C footprint regardless of polythene and biodegradable fragments. The findings unveiled the serious effects of plastic residues on permanent C sequestration across SPAC, implying that current C assessment methods clearly overlook plastic footprint and their global impact effects.